Adapting CEFR in the Nepalese Context: The Need for Contextualization and Practice - Paneru, Narendra R.; Bohara, Bhuban B.; Biswokarma, Babu R. (Education Review Journal, 2025)
This study aims to investigate the feasibility of implementing the Common European Framework of Reference (CEFR) for languages to reform English language assessment in Nepalese secondary schools, aligning teaching and testing with global standards. Through a qualitative approach, the study draws on a literature review of CEFR implementation in Asian contexts (Japan, Malaysia, and Vietnam), as well as semi-structured interviews with three stakeholders: two secondary school teachers and one policymaker. Findings reveal that Nepal’s current English assessment practices, which are heavily reliant on rote memorization and written tests, do not align with curriculum goals that emphasize communicative competence. Key challenges to CEFR adoption include inadequate teacher preparedness, resource constraints, misalignment between curriculum and assessment, and limited stakeholder engagement. Despite these barriers, CEFR offers opportunities to standardize assessments, promote balanced evaluation of all language skills, and enhance global comparability. Drawing on successful Asian models, the study recommends integrating the CEFR in a contextualized manner through sustained teacher professional development, curriculum revision, and inclusive stakeholder collaboration. Phased implementation and pilot testing are proposed to ensure equitable and sustainable reform, enabling Nepalese students to meet the linguistic demands of higher education and globalized contexts.